2019
DOI: 10.2807/1560-7917.es.2019.24.41.1900598
|View full text |Cite|
|
Sign up to set email alerts
|

Estimating the ‘PrEP Gap’: how implementation and access to PrEP differ between countries in Europe and Central Asia in 2019

Abstract: In 2019, only 14 European and Central Asian countries provided reimbursed HIV pre-exposure prophylaxis (PrEP). Using EMIS-2017 data, we present the difference between self-reported use and expressed need for PrEP in individual countries and the European Union (EU). We estimate that 500,000 men who have sex with men in the EU cannot access PrEP, although they would be very likely to use it. PrEP’s potential to eliminate HIV is currently unrealised by national healthcare systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
78
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 8 publications
1
78
1
Order By: Relevance
“…Although PrEP is highly effective for HIV prevention, PrEP availability and scale-up across Europe has been slow and uneven to date, and the ‘gap’ between self-reported use and expressed need is large across European countries [15]. Additionally, our survey highlights high demand for PrEP and a larger PrEP ‘gap’ than expected, with around one in five individuals in need of PrEP but unable or unsure of how to access publicly funded PrEP.…”
Section: Discussionmentioning
confidence: 90%
“…Although PrEP is highly effective for HIV prevention, PrEP availability and scale-up across Europe has been slow and uneven to date, and the ‘gap’ between self-reported use and expressed need is large across European countries [15]. Additionally, our survey highlights high demand for PrEP and a larger PrEP ‘gap’ than expected, with around one in five individuals in need of PrEP but unable or unsure of how to access publicly funded PrEP.…”
Section: Discussionmentioning
confidence: 90%
“…Multiple demonstration studies worldwide have shown the feasibility and acceptability of delivering PrEP to different key populations, such as men who have sex with men (MSM), transgender women (TGW), and adolescent girls and young women (AGYW) [6]. Considering this broad evidence base, the number of countries implementing PrEP has been increasing over the past few years [6][7][8]. By June 2018, a total of 19 high-income countries (HICs) and 21 low-and middle-income countries (LMICs) had adopted, or had a pending policy for, formal PrEP implementation [7].…”
Section: Introductionmentioning
confidence: 99%
“…Although in 2016 the European Medicines Agency gave a positive opinion on PrEP use [7], in 2019 still only 14 European and Central Asian countries provided reimbursed PrEP [8]. The PrEP gap (the proportion of people not diagnosed with HIV infection who would be very likely to use PrEP if it were available) is largest in CEE [8]. As stated by the Euroguidelines in Central and Eastern Europe (ECEE) Network Group, although health care providers are ready to implement this strategy in daily practice, there are numerous political, technical and legal barriers which delay the implementation of PrEP in the region [9].…”
Section: Introductionmentioning
confidence: 99%